THE EXTREMELY EMBARRASSING LIFE OF LOTTIE BROOKS - Kirby, Katie (London : Puffin, 2021)
Lottie Brooks is 11 and her life is already officially over - not only is she about to start high school without any friends or glamorous swooshy hair, she's just discovered she's too flat-chested to wear A BRA! She might as well give up now and go into hibernation with her hamsters Sir Barnaby Squeakington and Fuzzball the Third. Lottie navigates the many perils of growing up in this fantastically funny new illustrated series for a 9-12 audience, filled with friendship, embarrassing moments and plenty of lols.
Keywords: Brooks, Lottie (Fictitious character) -- fiction; Interpersonal relations -- fiction; Families -- fiction